Iniquités de santé en milieu minoritaire : diagnostic de la situation chez les immigrants francophones de Sudbury - Hien, Amélie; Lafontant, Jean (Revue canadienne de santé publique, 2013)
Objectif Cet article vise à mettre au jour des iniquités de santé liées non seulement au fait de vivre dans un milieu linguistique minoritaire, mais aussi au fait d’être immigrant et de vivre dans un nouvel environnement avec une culture d’origine différente de celle de sa communauté d’accueil. Méthode Il s’agit d’une étude qualitative qui présente les expériences personnelles de nombreux immigrants francophones dans leurs rapports aux services et aux soins de santé à Sudbury ainsi que leurs perceptions quant à la qualité et l’accessibilité de ces services et soins. Soixante-douze (72) individus âgés de 18 à 65 ans, dont 45 hommes et 27 femmes, ont participé à cette recherche à travers des entrevues individuelles et des groupes de discussions. Résultats Les résultats obtenus montrent, entre autres, qu’être immigrant et francophone limite l’accès aux services de santé, affecte la qualité de ces services et nuit à une prise en charge efficace des problèmes de santé. C’est ainsi que certains individus ne sont même pas en mesure de donner un consentement éclairé lors de décisions importantes à prendre concernant leur santé. Conclusion L’article fait des suggestions pour que ces immigrants puissent accéder à de meilleurs services et soins de santé, en vue de contribuer à l’amélioration de la santé de la population canadienne dont ils sont partie intégrante.

Misinterpretation: Language proficiency, recent immigrants, and global health disparities - Pottie, Kevin (Canadian Family Physician, 2007)
https://pmc.ncbi.nlm.nih.gov/articles/PMC2231483/

Workforce utilization of visible and linguistic minorities in Canadian nursing - Premji, Stephanie; Etowa, Josephine. B. (Journal of Nursing Management, 2012)
Background There is ample evidence of ethnic and linguistic segregation in the Canadian labour market. However, it is unknown if there is equitable representation of visible and linguistic minorities in nursing professions. Methods We cross-tabulated aggregate data from Statistics Canada’s 2006 Census. Analyses examined the distribution of visible and linguistic minorities, including visible minority sub-groups, among health managers, head nurses, registered nurses, licensed nurses and nurse aides for Canada and major cities as well as by gender. Results In Canada and its major cities, a pyramidal structure was found whereby visible and linguistic minorities, women in particular, were under-represented in managerial positions and over-represented in lower ranking positions. Blacks and Filipinos were generally well represented across nursing professions; however, other visible minority sub-groups lacked representation. Conclusions Diversity initiatives at all levels can play a role in promoting better access to and quality of care for minority populations through the increased cultural and linguistic competence of care providers and organizations.

Potential for patient-physician language discordance in Ontario - Sears, Jennifer; Khan, Kamran; Ardern, Chris . I.; Tamim, Hala (BMC Health Services Research, 2013)
Background Patient-Physician language discordance occurs when the patient and physician lack proficiency in the same language(s). Previous literature suggests language discordant clinical encounters compromise patient quality of care and health outcomes. The objective of this study was to quantify and visualize the linguistic and spatial mismatch between Ontario’s population not proficient in English or French but proficient in one of the top five non-official languages and the physicians who are proficient in the same non-official language. Methods Using data from the 2006 Canadian census and the 2006 Canadian Medical Directory, we determined the number of non-English/non-French (NENF) speaking individuals and the number of Ontario physicians proficient in the top five non-official languages in each census division (CD) of Ontario. For each non-official language, we produced bi-variate choropleth maps of Ontario, broken down into the 49 CDs, to determine which CDs had the highest risk of language discordant clinical encounters. Results According to the 2006 Canadian census, the top five non-official languages spoken by Ontario’s NENF population were: Chinese, Italian, Punjabi, Portuguese and Spanish. For each of the top five non-official languages, there were at least 5 census divisions with a NENF population speaking a non-official language without any primary care physicians proficient in that non-official language. The size of NENF populations within these CDs ranged from 10 individuals to 1,470 individuals. Conclusions Understanding the linguistic capabilities of Ontario’s immigrant population & the linguistic capabilities of Ontario’s primary care physicians is essential to ensure equal access and quality of healthcare. As immigration continues to increase, we may find that the linguistic needs of Ontario’s immigrant population diverge from the linguistic capabilities of Ontario’s primary care physicians. Further research on the language discordance in Ontario is needed in order to reduce the risk of language discordant clinical encounters and the negative health outcomes associated with these encounters.